Assessing the Effect of Management Styles on Project Performance in Rwanda: A Case of Urban Economic Development Initiative Project - INGABIRE, Assia (International Journal of Scientific Research and Management (IJSRM), 2025)
This study assessed the effect of management styles on project performance in Rwanda, with a particular focus on the Urban Economic Development Initiative Project (UEDIP). The research employed a mixed-methods approach, combining qualitative and quantitative data collection techniques to gain a comprehensive understanding of the relationship between management styles and project outcomes. Data were gathered from project managers, employees, and key stakeholders through surveys, interviews, and document analysis. The study aimed to determine how different leadership styles influenced project efficiency, employee engagement, and overall success. By analyzing both numerical data and personal insights from participants, the study provided a holistic view of the impact of management approaches on project implementation. The findings revealed that transformational leadership played a crucial role in enhancing project performance by fostering employee motivation, innovation, and teamwork. Leaders who adopted this style were able to inspire their teams, encourage creativity, and maintain high levels of engagement, ultimately leading to improved project outcomes. In contrast, transactional leadership was found to be effective in maintaining efficiency and accountability through structured processes, performance monitoring, and reward-based motivation. However, the study also found that autocratic leadership styles negatively affected employee morale, leading to dissatisfaction and, in some cases, project delays due to a lack of collaboration and rigid decision-making structures. These findings highlight the importance of selecting appropriate management styles to balance productivity and employee well-being in project execution. Based on the study’s findings, it is recommended that organizations adopt a hybrid management approach that integrates the strengths of both transformational and transactional leadership while minimizing the negative impacts of autocratic leadership. By combining the motivational and innovation-driven aspects of transformational leadership with the efficiency and accountability of transactional leadership, project managers can optimize project performance and sustainability. Additionally, fostering participatory decision-making and encouraging open communication within teams can enhance collaboration and adaptability, ultimately leading to better project outcomes. These recommendations provide valuable insights for policymakers, project managers, and development practitioners seeking to improve project execution and long-term impact in Rwanda’s urban development initiatives.